Strategi Pengendalian Kekerasan Terhadap Perempuan Oleh Dinas Pemberdayaan Perempuan Dan Perlindungan Anak (DPPPA) di Kota Bekasi - Utami, Priscillya Dwi; Sari Ningsih; Zuhri, Saefudin (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Violence is all forms of behavior carried out by a person or group, against another person or group of people, so that it can cause negative physical, emotional and psychological effects on the person being targeted. This study aims to determine the strategy of the Bekasi City DPPPA in controlling violence against women that occurs in Bekasi City. The theory used is the strategy management theory according to J. David Hunger and Thomas L. Wheelen (2011) using a qualitative descriptive research method. The results of the study indicate that the Bekasi City DPPPA is quite good at implementing strategies for controlling violence against women which include prevention, handling, protection, and supervision. However, in its implementation it still needs to be improved so that the formulated program can run optimally.